Antimalarial Activity of an Alkaloidal Drug Isolated from Enicostema of Ganteaceae Family - JAIN, SHARAD; JAIN, RAJNI; JAIN, D.K.; SAXENA, R.C. (Asian Journal of Chemistry, 2010)
Enicostima commonly known as Nahi, was collected locally and extracted in petroleum ether in soxhlet apparatus. The crude product was purified using Mayr's reagent and yielded as liriodenine when tested against plasmodium showed schizonticidal activity.